New Bioactive Metabolites from the Thermophilic Fungus Penicillium sp. Isolated from Ghamiqa Hot Spring in Saudi Arabia - Raha Orfali; Shagufta Perveen (Journal of Chemistry)
The thermophilic fungus Penicillium species was isolated from Ghamiqa hot spring sediments in Saudi Arabia. Extract of Penicillium species cultured on solid rice medium yielded two new compounds 3-(furan 12-carboxylic acid)-6-(methoxycarbonyl)-4-hydroxy-4-methyl-4 and 5-dihydro-2H-pyran 1 3α-methyl-7-hydroxy-5-carboxylic acid methyl ester-1-indanone 2. In addition, three known compounds, austinol 3, emodin 4, and 2-methyl-penicinoline 5, were isolated. The structures of the new compounds were unambiguously determined by comprehensive analysis of spectroscopic data, one- and two-dimensional NMR spectroscopy, and high-resolution mass spectrometry. All isolated metabolites were studied for their antibiotic effect against several pathogenic bacteria and for their cytotoxicity against the lymphoma human cancer cell line HTB-176. Austinol 3 exhibited strong antibacterial activity against P. aeruginosa bacterial strain with an MIC value of 0.13 ± 0.4 µg·mL−1, whereas emodin 4 demonstrated significant cytotoxicity against the tested HTB-176 cell line with an IC50 value of 2 ± 7.6 µM, while the other compounds were moderate to inactive with IC50 ranging from 4.3 ± 0.25–22 ± 2.94 µM in this assay.